DETERMINAN STRUKTUR MODAL YANG OPTIMUM - Nengah Sukendri; I Gede Bayu Wijaya; I Made Arya Adi Thanaya (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
Companies in their management require capital as financing thatcan affect business sustainability. For this reason, consideration isneeded in choosing the source of capital funds. The purpose of thisstudy is to describe the determinants of optimal capital structure.Funding and fulfilling investment needs can be done from internalsources and external sources so that funding and equity decisionswithin a company are influenced by internal and external factorswithin the company's environment. The optimal proportion andbalance between the two sources of funds, both sources of owncapital funds and sources of foreign capital funds, is expected toprovide an optimum capital structure for the company. Thedecision to finance with debt can be made as needed by consideringthe risks.